Isolation and identification of floral attractants from a nectar plant for the dried bean beetle, Acanthoscelides obtectus (Coleoptera: Chrysomelidae, Bruchinae). Issue 9 (30th March 2018) - Vuts, József; Woodcock, Christine M; Caulfield, John C; Powers, Stephen J; Pickett, John A; Birkett, Michael A
Abstract : Acanthoscelides obtectus is a major pest of stored beans. We demonstrate that flower volatiles induce positive behavioural responses from females, creating a platform for semiochemical‐based control strategies. Abstract: BACKGROUND: The response of virgin females of the legume pest Acanthoscelides obtectus (Coleoptera: Bruchidae) to headspace extracts of volatiles collected from flowers of a nectar plant, Daucus carota, was investigated using behaviour (four‐arm olfactometry) and coupled gas chromatography–electroantennography (GC‐EAG). RESULTS: Odours from inflorescences were significantly more attractive to virgin female beetles than clean air. Similarly, a sample of volatile organic compounds (VOCs) collected by air entrainment (dynamic headspace collection) was more attractive to beetles than a solvent control. In coupled GC‐EAG experiments with beetle antennae and the VOC extract, six components showed EAG activity. Using coupled GC–mass spectrometry (GC–MS) and GC peak enhancement with authentic standards, the components were identified as α‐pinene ( S:R 16:1), sabinene, myrcene, limonene ( S:R 1:3), terpinolene and ( S )‐bornyl acetate. Females preferred the synthetic blend of D. carota EAG‐active volatiles to the solvent control in bioassays. When compared directly, odours of D. carota inflorescences elicited stronger positive behaviour than the synthetic blend. CONCLUSION: This is the first report of behaviourally active volatiles linked to pollen location for A. obtectus, and development of the six‐component blend is being pursued, which could underpin the design of semiochemical‐based field management approaches against this major pest of stored products. © 2018 Society of Chemical Industry